Prognostic Assessment of Right Ventricular Systolic Dysfunction on Post–Transcatheter Aortic Valve Replacement Short‐Term Outcomes: Systematic Review and Meta‐Analysis. Issue 12 (16th June 2020) - Grevious, Salih N.; Fernandes, Marcelo F.; Annor, Ama K.; Ibrahim, Michel; Saint Croix, Garly R.; de Marchena, Eduardo; G. Cohen, Mauricio; Alfonso, Carlos E.
Abstract : Background: Right ventricular systolic dysfunction (RVSD) is a known risk factor for adverse outcome in surgical aortic valve replacement. Transcatheter aortic valve replacement (TAVR), on the other hand, has been shown to be either beneficial or have no effect on right ventricular systolic function. However, the prognostic significance of RVSD on TAVR has not been clearly determined. We conducted a systematic review and meta‐analysis to define the impact of RVSD on outcomes in terms of 1‐year mortality in patients with severe aortic stenosis undergoing TAVR. Methods and Results: An extensive literature review was performed, with an aim to identify clinical studies that focused on the prognosis and short‐term mortality of patients with severe symptomatic aortic stenosis who underwent TAVR. A total of 3166 patients from 8 selected studies were included. RVSD, as assessed with tricuspid annular plane systolic excursion, fractional area change or ejection fraction, was found to be a predictor of adverse procedural outcome after TAVR (hazard ratio, 1.31; 95% CI, 1.1–1.55; P =0.002). Overall, we found that RVSD did affect post‐TAVR prognosis in 1‐year mortality rate. Conclusions: Patients with severe, symptomatic aortic stenosis and concomitant severe RVSD have a poor 1‐year post‐TAVR prognosis when compared with patients without RVSD. Right ventricular dilation and severe tricuspid regurgitation were associated with increased 1‐year morality post‐TAVR and should be considered as independent risk factors. Further evaluations of long‐term morbidity, mortality, as well as sustained improvement in functional class and symptoms need to be conducted to determine the long‐term effects.